In Vitro Selective Combinatory Effect of Ciprofloxacin with Nitroxoline, Sanguinarine, and Zinc Pyrithione against Diarrhea-Causing and Gut Beneficial Bacteria - Osei-Owusu, Hayford; Kudera, Tomas; Strakova, Marie; Rondevaldova, Johana; Skrivanova, Eva; Novy, Pavel; Kokoska, Ladislav (Microbiology spectrum, 2022)
Antibiotic resistance in diarrhea-causing bacteria and its disruption of gut microbiota composition are health problems worldwide. The development of combinatory agents that increase the selective inhibitory effect (synergism) against diarrheagenic pathogens and, simultaneously, have a lowered impact (antagonism) or no negative action on the gut microbiota is therefore proposed as a new strategy efficient for chemotherapy against diarrheal conditions. In this study, the in vitro selective combinatory effect of ciprofloxacin with nitroxoline, sanguinarine, and zinc pyrithione, representing various classes of alkaloid-related compounds (nitroquinolines, benzylisoquinolines and metal-pyridine derivative complexes) against selected standard diarrhea-causing (Bacillus cereus, Enterococcus faecalis, Listeria monocytogenes, Shigella flexneri, and Vibrio parahaemolyticus) and gut-beneficial (Bifidobacterium adolescentis, Bifidobacterium animalis subsp. lactis, Bifidobacterium breve, Lactobacillus casei, and Lactobacillus rhamnosus) bacteria, was evaluated according to the sum of fractional inhibitory concentration indices (FICIs) obtained by the checkerboard method. The results showed that the individual combination of ciprofloxacin with nitroxoline, sanguinarine, and zinc pyrithione produced a synergistic effect against the pathogenic bacteria, with FICI values ranging from 0.071 to 0.5, whereas their antagonistic interaction toward the Bifidobacterium strains (with FICI values ranging from 4.012 to 8.023) was observed. Ciprofloxacin-zinc pyrithione produced significant synergistic action against S. flexneri, whereas a strong antagonistic interaction was observed toward B. breve for the ciprofloxacin-nitroxoline combination. These findings suggest that certain combinations of agents tested in this study can be used for the development of antidiarrheal therapeutic agents with reduced harmful action on the gastrointestinal microbiome. However, further studies focused on their pharmacological efficacy and safety are needed before they are considered for clinical trials. IMPORTANCE Diarrheal infections, which are commonly treated by antibiotics, are still responsible for over 4 to 5 million cases of human deaths annually. Moreover, the rising incidence of antibiotic resistance and its negative effect on beneficial bacteria (e.g., Bifidobacteria) of the gut microbial community are another problem. Thus, the development of selective agents able to inhibit diarrheal bacteria and, simultaneously, that have no negative impact on the gut microbiota, is important. Our results showed that individual combinations of ciprofloxacin with nitroxoline, sanguinarine, and zinc pyrithione produced synergism against the pathogenic bacteria, whereas their antagonistic interaction toward the beneficial strains was observed. The antagonism can be considered a positive effect contributing to the safety of the therapeutic agents, whereas their synergism against diarrheal bacteria significantly potentiates total antimicrobial efficacy. The certain combinations tested in this study can be used for the development of antidiarrheal agents with reduced harmful action on the gastrointestinal microbiome.
Keywords: ciprofloxacin; Anti-Bacterial Agents; nitrochinoliny; Bacteria; Benzylisoquinolines; Nitroquinolines; Pyridines; pyridiny; Bifidobacterium; gut microbiota; Ciprofloxacin; benzylisochinoliny; Diarrhea; diarrhea; Humans; synergism; Antidiarrheals; antibakteriální látky; průjem; antimicrobial agents; selectivity; antagonism; lidé; obstipancia